2015
DOI: 10.1002/chem.201406114
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen‐Atom Transfer Chemistry and Thermolytic Properties of a Di‐tert‐Butylphosphate‐Ligated Mn4O4 Cubane

Abstract: [Mn4O4{O2P(OtBu)2}6] (1), an Mn4O4 cubane complex combining the structural inspiration of the photosystem II oxygen-evolving complex with thermolytic precursor ligands, was synthesized and fully characterized. Core oxygen atoms within complex 1 are transferred upon reaction with an oxygen-atom acceptor (PEt3), to give the butterfly complex [Mn4O2{O2P(OtBu)2}6(OPEt3)2]. The cubane structure is restored by reaction of the latter complex with the O-atom donor PhIO. Complex 1 was investigated as a precursor to ino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 107 publications
(115 reference statements)
1
4
0
Order By: Relevance
“…[15,68] However, when changing to six bis(p-methoxyphenyl)phosphinate ligands, [7,68] the Mn3444 oxidation state showed one JT axis and the Mn3344 oxidation state showed two antiparallel JT axes (compare Figure 4). The same antiparallel JT arrangement for Mn3344 was reported for a complex with six di(t-butyl) phosphate ligands [69] and another complex with six dimethylarsinate ligands. [23] This might indicate that in homoleptic Mn 4 O 4 cubanes, antiparallel JT arrangements might be energetically favorable.…”
Section: Comparison To X-ray Structuresupporting
confidence: 74%
“…[15,68] However, when changing to six bis(p-methoxyphenyl)phosphinate ligands, [7,68] the Mn3444 oxidation state showed one JT axis and the Mn3344 oxidation state showed two antiparallel JT axes (compare Figure 4). The same antiparallel JT arrangement for Mn3344 was reported for a complex with six di(t-butyl) phosphate ligands [69] and another complex with six dimethylarsinate ligands. [23] This might indicate that in homoleptic Mn 4 O 4 cubanes, antiparallel JT arrangements might be energetically favorable.…”
Section: Comparison To X-ray Structuresupporting
confidence: 74%
“…Furthermore, the local environment and charge state of the cobalt for the [Co 4 O 4 ] building units are the same in all of the materials under study, as indicated by the X-ray absorption near edge structure (XANES). This technique has been used for the photosystem II active site (44)(45)(46)(47)(48), the cobalt oxide wateroxidation catalyst (49,50), and Mn-oxo cubanes (9,(51)(52)(53).…”
Section: Resultsmentioning
confidence: 99%
“…), showed almost equivalent Mn-O bond lengths, which was attributed to valence delocalization at elevated temperature (298 K). Lowering the temperature to 150 K led to a small differentiation of Mn-O bonds 147 and the bond length inequivalence was also shown to depend on the ligand L. 148,149 The crystal structure of the singly oxidized product of the complex [Mn 4 O 4 ] 7+ demonstrates a trigonal distortion compared to the tetragonal symmetry of the parent complex, i.e. [Mn 4 O 4 ] 6+ .…”
Section: Tetramanganese Complexesmentioning
confidence: 99%